La Difesa delle Lavoratrici: socialiste a confronto - Fiorenza Taricone (Laboratoire Italien)
This article analyses La Difesa delle Lavoratrici, the first national periodical for socialist women, which was founded by Anna Kuliscioff and published in Italy between 1912 and 1925. The main exponents of socialism of the time, both members of the Italian Socialist Party and associations close to the Party, wrote and contributed to discussion in the magazine; however, we also find personal accounts from working women who wrote letters to the newspaper talking about the problems of everyday life. We can consider the journalists who wrote in the periodical political pioneers in the first mass party. Of particular interest are the discussions between interventionists and pacifists and the controversy over the autonomy of the female sections as compared to the male ones.